POLITICIANS AND SOCIAL LEADERS. INTRODUCING A MODEL OF MUTUAL RELATIONS AND SHAPING BELIEFS OF VOTERS - Karol Fjałkowski (Ekonomia i Prawo, 2014)
This paper introduces an informal model of behavior of Politicians and Social Leaders in their mutual relations in the context of influencing the beliefs of voters. Facing uncertainty about Politicians voters turn to Social Leaders as information short-cuts. Leaders include NGOs, the media and religious organizations. The Politicians-Leaders relations are modeled as complex implicit Principal-Agent contracts. The model predicts various forms of opportunistic behavior of both sides. Numerous behavioral predictions of the model as well as empirical examples from contemporary Polish socio-political life have been provided.